The economic burden of medical treatment of children with asthma in China - Wu, Ping; Xu, Baoping; Shen, Adong; He, Zonglin; Zhang, Casper J. P.; Ming, Wai-kit; Shen, Kunling (BMC pediatrics, 2020)
At present, there are few studies on the economic burden and medical treatment of children with asthma in China. Thus this study aimed to investigate the economic burden of medical treatment of children with asthma in China. The 2015 China Medical Insurance Research Association (CHIRA) database was searched for patients with asthma from 0 to 14 years old. A cross-sectional study with cost analysis was conducted. The annual per capita direct medical cost was RMB 525 (US$75) related to asthma. Totaling 58% of the medical expenditure for asthma was covered by insurance in China, the majority of which were direct medical costs. Those that have the highest rates of using antibiotics were central China (100.0%), children aged 3 years and under (63.6%), as well as fourth-tier and fifth-tier cities (77.1%). Outpatient clinics (98.58% vs 1.42%, P < 0.01), tertiary hospitals (62.08% vs 37.92%, P < 0.01), and general hospitals (72.27% vs 27.73%, P < 0.01) were more often visited than the inpatient clinics, secondary and primary as well as the specialized clinics, respectively. The economic burden of childhood asthma in China is relatively low, and the national medical insurance reduces their economic burden to a large extent. Abuse of antibiotics in treating asthma was found in China. There remain opportunities to strengthen the hierarchical medical system, reducing hospitalization and emergency visits, and ultimately reducing the economic burden of children with asthma.